Determination by Priority Weight of Motoric Function in Children by Age Groups - KELEŞ, Ali; Deliceoğlu, Gökhan (Progress in Nutrition, 2021)
This study is to investigate the relationship between certain physical and motoric skills, and results of physical and motoric tests of male and female athletes from sports schools in Ankara province, and priority weights of the applied tests with respect to age groups. Research group at the Ankara sports schools serves as the basketball and volleyball training variable between the ages of aged 6-15 82 boys and girls to 103 total 185 created the voluntary athlete. Research, motorik features children according to age groups include the determination of the the weight of importance. To identify physical and motoric skills of athletes, height, weight, sit and reach test, flamingo test, right hand grip strength test, left hand grip strength test, pro-agility test, 30 meter sprint test, 30-s continuous jump test, vertical jump test, was used.Priority weights of physical and motoric tests are obtained by using computational model.Mean and standard deviation values of height, weight, sit and reach test, flamingo test, grip tests, agility test, sprint test, 30-s continuous jump test and vertical jump are computed by using IBM SPSS 20 for windows. Priority weights of the physical and motoric tests are computed by using Microsoft Office Excel 2007. In conclusion, for children in the age group over 10 who participated to research, priority weights of agility, speed, flexibility, and take-off parameters observed to stagnate and strength competence is observed to decreasing continuously. Therefore, a conclusion of, performance of the motoric skills are preserved after the age 10 in the development cycle of the children, is made.